Low circulating insulin-like growth factor I increases atherosclerosis in ApoE-deficient mice - Shai, Shaw-Yung (American Physiological Society, 2011)
Some clinical studies have suggested that lower IGF-I levels may be associated with an increased risk of ischemic heart disease. We generated atherosclerosis-prone apolipoprotein E-deficient (ApoE(−/−)) mice with 6T alleles (6T/ApoE(−/−) mice) with a 20% decline in circulating IGF-I and fed these mice and control ApoE(−/−) mice with normal chow or a Western diet for 12 wk to evaluate the effect of low serum IGF-I on atherosclerosis progression. We found that the 6T/ApoE(−/−) phenotype was characterized by an increased atherosclerotic burden, elevated plaque macrophages, and increased proinflammatory cytokine TNF-α levels compared with ApoE(−/−) controls. 6T/ApoE(−/−) mice had similar body weight, blood pressure, serum total cholesterol levels, total plaque and smooth muscle cell apoptosis rates, and circulating levels of endothelial progenitor cells as ApoE(−/−) mice. 6T/ApoE(−/−) mice fed with normal chow had reduced vascular endothelial nitric oxide synthase mRNA levels and a trend to increased aortic expression of chemokine (C-C motif) receptor (CCR)1, CCR2, and monocyte chemoattractant protein-1/chemokine (C-C motif) ligand 2. Western diet-fed 6T/ApoE(−/−) mice had a trend to increased expression of macrophage scavenger receptor-1/scavenger receptor-A, osteopontin, ATP-binding cassette (subfamily A, member 1), and angiotensin-converting enzyme and elevated circulating levels of the neutrophil chemoattractant chemokine (C-X-C motif) ligand 1 (KC). Our data establish a link between lower circulating IGF-I and increased atherosclerosis that has important clinical implications.